1997
DOI: 10.1021/ma970138a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of End-Functionalized Polymers by Means of Living Anionic Polymerization. 8. Reactions of Living Anionic Polymers with α,ω-Dihaloalkanes

Abstract: In order to prepare well-defined polymers with halogen end groups, anionic living polymers of isoprene and styrene were allowed to react with excess amounts of α,ω-dihaloalkanes in THF at −78 °C. The monosubstitution reactions of 1,3-dichloropropane with these anionic living polymers proceeded cleanly to afford quantitatively the polymers with chlorine end groups that possessed controllable molecular weights and narrow molecular weight distributions. On the other hand, the reactions of the anionic living polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…[16] The dark red color of the living functionalized polystyrene faded gradually, indicating that the reaction proceeded smoothly. The desired polymer was isolated in A90% yield by HPLC fractionation to remove unreacted end-functionalized polystyrene with 4-bromobutyl group used in excess in the reaction.…”
Section: Synthesis Of In-chain Functionalized Polymers With 13-butadmentioning
confidence: 99%
“…[16] The dark red color of the living functionalized polystyrene faded gradually, indicating that the reaction proceeded smoothly. The desired polymer was isolated in A90% yield by HPLC fractionation to remove unreacted end-functionalized polystyrene with 4-bromobutyl group used in excess in the reaction.…”
Section: Synthesis Of In-chain Functionalized Polymers With 13-butadmentioning
confidence: 99%
“…At a time when the recently discovered controlled radical polymerization [2*] is viewed as a much less demanding process, anionic polymerization still remains an important method, well-suited to kinetic studies [3*], the synthesis of polymers of predictable molecular weight (MW) with a narrow molecular weight distribution (MWD), tailoring of block copolymers [4,5*,6-9], design of nonlinear molecular architectures [10**, 11] and telechelic polymers [12][13][14][15][16][17], and stereoregular polymerization [18,19]. Major progress in mechanistic studies and macromolecular engineering reported in the past year(s) is to be found in the very challenging field of the anionic polymerization of (meth)acrylic monomers.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these reactions have been utilized as the classical approach to the synthesis of chain-end-functionalized polymers. In this case, some of the functional groups were protected prior to the post-polymerization reactions, such that well-defined, chain-end-functionalized PSs and PIs with COOH, OH, SH, NH 2 , (CH 2 ) n X, perfluoroalkyl, d-glucose, aziridinyl, 4-vinylphenyl, 1,1-diphenylethenyl, and 1,3-butadienyl (>95%) could be successfully obtained [175][176][177][178][179][180][181]. Unfortunately, however, many of these reactions were inadequately characterized or optimized for general utility.…”
Section: Reaction Of Living Anionic Polymers With Electrophiles: Syntmentioning
confidence: 99%